Rancang Bangun Aplikasi Pemesanan Makanan Di Kedai Bakso Solo Mas Tulus Berbasis Android Dengan Metode Highest Ratio Next (Hrn) - Tria Nova; Toibah Umi Kalsum; Rizka Tri Alinse (UNIVED Press, 2022)
ABSTRACT The Food Ordering Application at Kedai Bakso Solo Mas Tulus aims to change the ordering system that previously only used general applications to become special applications and provide the best to customers therefore customers get maximum service. To get the best service by using a special application using the Highest Ratio Next method, the order will be calculated based on the arrival of the order and the length of time the order is processed so that consumers who order with different arrival times and with different processing times will get a fair order completion time. For Kedai Bakso Mas Tulus, with this special application and with the Highest Ratio Next method, it will change the presentation process of orders that were made previously. Therefore, with the development of a Food Ordering Application at Kedai Bakso Solo Mas Tulus based on Android with the Highest Ratio Next (HRN) it can assist in the process of serving food orders made by consumers. This system can help Kedai Bakso Mas Tulus in determining the best food presentation quickly and precisely. Keywords: Food Ordering Application Design, HRN, Kedai Bakso Mas Tulus.